Addressing the COVID-19 Pandemic: Comparing Alternative Value Frameworks - Maddalena Ferranna; J.P. Sevilla; David E. Bloom (Institute of Labor Economics (IZA), 2021)
The COVID-19 pandemic has forced countries to make difficult ethical choices, e.g., how to balance public health and socioeconomic activity and whom to prioritize in allocating vaccines or other scarce medical resources. We discuss the implications of benefit-cost analysis, utilitarianism, and prioritarianism in evaluating COVID-19-related policies. The relative regressivity of COVID-19 burdens and control policy costs determines whether increased sensitivity to distribution supports more or less aggressive control policies. Utilitarianism and prioritarianism, in that order, increasingly favor income redistribution mechanisms compared with benefit-cost analysis. The concern for the worse-off implies that prioritarianism is more likely than utilitarianism or benefit-cost analysis to target young and socioeconomically disadvantaged individuals in the allocation of scarce vaccine doses.
Keywords: I1; I3; D6; 330; prioritarianism; benefit-cost analysis; utilitarianism; COVID-19; vaccine allocation; lockdown; control policies